Población-territorio : cien años de evolución, 1895-1990 - Graizbord, Boris; Mina Valdés, Alejandro (El Colegio de México A.C., 1993)
In this article, the authors provide a definition of the spatial dimension implicit in the relationship between man and nature. Based on this definition, Graizbord and Mina describe population distribution trends from 1895 to 1990 as they relate to a division of political and administrative factors. The study provides an estimate of population dispersion throughout time by analyzing the behavior of state populations with respect to the distance between state capitals and the Federal District. It also provides 100-year curves describing time variations of population dispersion and explaning the process of decentralization of displacement from the country's main population center to its peripheral areas.